Serum Nickel and Titanium Levels after Transcatheter Closure of Atrial Septal Defects with Amplatzer Septal Occluder. (2nd January 2019) - Elkiran, Ozlem; Karakurt, Cemsit; Kocak, Gulendam; Taskapan, Cagatay
Abstract : Introduction . There is a concern about release of nickel and titanium after implantation of nitinol-containing devices. Objective . To evaluate serum nickel and titanium release after implantation of Amplatzer occluder. Materials and methods . In 38 pediatric patients with no history of nickel sensitivity, blood samples were drawn 24 hours before and 24 hours, 1, 3, 6, and 12 months after implantation. Nickel and titanium concentrations were measured by atomic absorption spectrophotometry. Results . The median serum nickel level which was 0.44 ng/mL before the implantation increased to 1.01 ng/mL 24 hours after implantation and 1.72 ng/mL one month after implantation. The maximum level was detected 3 months after implantation, with a median level of 1.96 ng/mL. During follow-up, the nickel levels decreased to those measured before implantation. Serum nickel levels at the 24th hour, 1st month, and 3rd month following implantation were found to have increased significantly. No patients showed a detectable serum titanium level. Discussion . This is the first study that evaluated both serum nickel and titanium release after implantation of the Amplatzer occluder. Our study shows that nickel is released from the device in the first few months after implantation. Therefore, in patients with nickel allergy, other devices may be considered.